PEMBERDAYAAN MASYARAKAT MELALUI PROMOSI DIGITAL DAN PERENCANAAN PROGRAM BERKELANJUTAN DI NAGARI SIPADEH KECAMATAN SANGIR KABUPATEN SOLOK SELATAN - Ares Albirru Amsal; Lailaturrahmi Lailaturrahmi; Felga Zulfia Rasdiana (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2025)
In Indonesia, including in West Sumatra, red ginger drinks are very popular among the people. Development activities in this field deserve more attention. Therefore, this activity aims to support the business development of Nagi Sipadeh, a producer of red ginger drink which is popular in West Sumatra, Indonesia. The main goal is to increase Nagi Sipadeh's visibility in cyberspace by creating attractive promotional videos and providing business development guidelines for the next five years. The activity method was carried out in several stages, namely observation and structured interviews to identify the main problems of Nagi Sipadeh, designing and producing a promotional video highlighting their ginger powder production process, as well as preparing business development guidelines based on findings from observations, interviews and comprehensive market analysis. The result of this activity is the successful production and distribution of promotional videos to various digital platforms such as YouTube, Instagram, WhatsApp, and Facebook, which has significantly increased Nagi Sipadeh's visibility in cyberspace. Business development guidelines up to 2025 have also been prepared, providing solid guidance for Nagi Sipadeh's future business development. The discussion underlined the importance of digital marketing in supporting business growth, as well as the role of partners and training in overcoming the problems faced by Nagi Sipadeh. Recommendations for further activities are to continue continuous monitoring and evaluation, deepen training in digital marketing, explore more innovative product development opportunities, and expand partner networks to support sustainable business growth.